β-micrustoxin (Mlx-9), a PLA2 from Micrurus lemniscatus snake venom: biochemical characterization and anti-proliferative effect mediated by p53 - Santos,Natália Fernanda Teixeira dos (2022)
Abstract Background Endogenous phospholipases A2 (PLA2) play a fundamental role in inflammation, neurodegenerative diseases, apoptosis and cellular senescence. Neurotoxins with PLA2 activity are found in snake venoms from the Elapidae and Viperidae families. The mechanism of action of these neurotoxins have been studied using hippocampal and cerebellar neuronal cultures showing [Ca2+]i increase, mitochondrial depolarization and cell death. Astrocytes are rarely used as a model, despite being modulators at the synapses and responsible for homeostasis and defense in the central nervous system. Preserving the cell division ability, they can be utilized to study the cell proliferation process. In the present work cultured astrocytes and glioblastoma cells were employed to characterize the action of β-micrustoxin (previously named Mlx-9), a PLA2 isolated from Micrurus lemniscatus snake venom. The β-micrustoxin structure was determined and the cell proliferation, cell cycle phases and the regulatory proteins p53, p21 and p27 were investigated. Methods β-micrustoxin was characterized biochemically by a proteomic approach. Astrocytes were obtained by dissociation of pineal glands from Wistar rats; glioblastoma tumor cells were purchased from ATCC and Sigma and cultured in DMEM medium. Cell viability was evaluated by MTT assay; cell proliferation and cell cycle phases were analyzed by flow cytometry; p53, p21 and p27 proteins were studied by western blotting and immunocytochemistry. Results Proteomic analysis revealed fragments on β-micrustoxin that aligned with a PLA2 from Micrurus lemniscatus lemniscatus previously identified as transcript ID DN112835_C3_g9_i1/m.9019. β-micrustoxin impaired the viability of astrocytes and glioblastoma tumor cells. There was a reduction in cell proliferation, an increase in G2/M phase and activation of p53, p21 and p27 proteins in astrocytes. Conclusion These findings indicate that β-micrustoxin from Micrurus lemniscatus venom could inhibit cell proliferation through p53, p21 and p27 activation thus imposing cell cycle arrest at the checkpoint G2/M.